Temporin G, an amphibian antimicrobial peptide against influenza and parainfluenza respiratory viruses: Insights into biological activity and mechanism of action. Issue 2 (4th February 2021) - De Angelis, M.; Casciaro, B.; Genovese, A.; Brancaccio, D.; Marcocci, M. E.; Novellino, E.; Carotenuto, A.; Palamara, A. T.; Mangoni, M. L.; Nencioni, L.
Abstract: Treatment of respiratory viral infections remains a global health concern, mainly due to the inefficacy of available drugs. Therefore, the discovery of novel antiviral compounds is needed; in this context, antimicrobial peptides (AMPs) like temporins hold great promise. Here, we discovered that the harmless temporin G (TG) significantly inhibited the early life‐cycle phases of influenza virus. The in vitro hemagglutinating test revealed the existence of TG interaction with the viral hemagglutinin (HA) protein. Furthermore, the hemolysis inhibition assay and the molecular docking studies confirmed a TG/HA complex formation at the level of the conserved hydrophobic stem groove of HA. Remarkably, these findings highlight the ability of TG to block the conformational rearrangements of HA2 subunit, which are essential for the viral envelope fusion with intracellular endocytic vesicles, thereby neutralizing the virus entry into the host cell. In comparison, in the case of parainfluenza virus, which penetrates host cells upon a membrane‐fusion process, addition of TG to infected cells provoked 1.2 log reduction of viral titer released in the supernatant. Nevertheless, at the same condition, an immunofluorescent assay showed that the expression of viral hemagglutinin/neuraminidase protein was not significantly reduced. This suggested a peptide‐mediated block of some late steps of viral replication and therefore the impairment of the extracellular release of viral particles. Overall, our results are the first demonstration of the ability of an AMP to interfere with the replication of respiratory viruses with a different mechanism of cell entry and will open a new avenue for the development of novel therapeutic approaches against a large variety of respiratory viruses, including the recent SARS‐CoV2.